SANITARY-HYGIENIC CHARACTERISTICS OF WATER ON DAIRY AND PIG FARMS - Sokolyuk, V.; Ligomina, I.; Furman, S.; Lisogurskaya, D.; Dukhnytskyi, V. (Scientific Progress & Innovations, 2019)
The sanitary and hygienic indicators of water quality from a water supply source used for watering animals on dairy and pig farms located nearby were studied in the southern bio-geochemical zone of Ukraine. The main purpose of the research was to investigate the water quality and the condition of the water supply source, as well as establish the factors and mechanisms that influence the formation of its mineral composition. Water samples were taken from two places (pit well and drinkers) in different seasons, corresponding to the standard procedure. The assessment of water quality and safety was carried out in accordance with the requirements of the State Sanitary standards and rules “Hygienic requirements to drinking water for human consumption” (DSanPin 2.2.4–171–10). According to the results of our research, a number of violations of sanitary requirements as to the water treatment in the source were established; also, the boundaries of sanitary protection zones which prevent the pollution of water-bearing stratum were not maintained. Unsatisfactory sanitary and technical condition of water supply system, its long-term operation also contributed to the deterioration of water quality on the farm. It was established that as to organoleptic characteristics the water was of good quality, but at the same time microbiological parameters did not meet the sanitaryhygienic requirements. The total number of mesophilic, aerobic and facultative anaerobic microorganisms in the water exceeded the permissible levels by 1.1–1.2 times in the water supply source and by 4.0–4.7 times in the drinkers. Nitrogen ammonium and nitrites concentrations in the water samples were within the standard levels. The content of nitrates in the water was high during all the study period, and exceeded the maximum permissible concentration in (MAC 50 mg N/dm3) by 2.1–3.9 times. The content of organic substances as to the index of permanganate oxidation varied from 2.4 to 6.8 mg O/dm3 in different study periods (MAC≤5,0 mg O/dm3). The total hardness of the water under investigation was high and ranged from 8.1 to 9.4 mg eq/dm3 during the study period. The level of total mineralization of the water was changing during the year from 927.0 to 1498.0 mg/dm3 with its highest level in the summer period. The concentration of calcium ions in the water was increased during all the study periods (150.3–160.3 mg/dm3). The content of magnesium, potassium and sodium ions did not exceed the limits of standard levels. The content of chlorides and sulfates in the water did not exceed the permissible values either. During the research the microelement content of the water was determined. The concentration of plumbum, cadmium, arsen, mercury, cuprum, zinc, ferrum, and cobalt was insignificant. The content of manganese in the water exceeded the standard values by 1.5–3.8 times, with its highest concentration in the winter and spring periods. The violation of ecological state in the area of the farm location and adjoining territories contributed to the pollution of soil and surface waters. The absence of the sanitary protection zone of the water supply source and unsatisfactory sanitarytechnical condition of the water supply network on the farm cause microbial pollution of water.